2002
DOI: 10.1096/fj.01-0673fje
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity alters differentiation and increases apoptosis in human follicular thyroid carcinoma cells

Abstract: This study focuses on the effects of simulated microgravity (0g) on the human follicular thyroid carcinoma cell line ML-1. Cultured on a three-dimensional clinostat, ML-1 cells formed three-dimensional MCTSs (MCTS diameter: 0.3 +/- 0.01 mm). After 24 and 48 h of clinorotation, the cells significantly decreased fT3 and fT4 secretion but up-regulated the thyroid-stimulating hormone-receptor expression as well as the production of vimentin, vinculin, and extracellular matrix proteins (collagen I and III, laminin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
209
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(229 citation statements)
references
References 44 publications
18
209
1
1
Order By: Relevance
“…In fact, in FLG 29.1 cells exposed to the RPM, both Fas and FasL resulted overexpressed, compared to the controls, thus suggesting the triggering of the extrinsic pathway. In accordance with data reported by other authors [Grimm et al, 2002;Uva et al, 2002;Carlsson et al, 2003], we found cytoskeletal alterations as well. In particular, the cytoskeletal intermediate filament protein vimentin increased, while a-actin, F-actin, and tubulin decreased.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, in FLG 29.1 cells exposed to the RPM, both Fas and FasL resulted overexpressed, compared to the controls, thus suggesting the triggering of the extrinsic pathway. In accordance with data reported by other authors [Grimm et al, 2002;Uva et al, 2002;Carlsson et al, 2003], we found cytoskeletal alterations as well. In particular, the cytoskeletal intermediate filament protein vimentin increased, while a-actin, F-actin, and tubulin decreased.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the involvement of both the extrinsic and intrinsic pathways was demonstrated. In cells exposed to low g, enhanced expression of the death receptor Fas, activating the extrinsic pathway, was detected [Lewis et al, 1998;Grimm et al, 2002]. It was also found that hypogravity-induced apoptosis is accompanied by an alteration of the cytoskeleton, resulting in redistribution and then dissolution of the mitochondria [Schatten et al, 2001;Kossmehl et al, 2003], as occurs in the intrinsic mitochondrial-mediated cell death program [Shimizu et al, 2000].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The induction of apoptosis has been reported in different cell lines in simulated hypogravity [26,27]. It is established that cell exposure to both real and simulated hypogravity conditions causes cytoskeleton disorganization associated with microtubule disruption [28].…”
Section: Discussionmentioning
confidence: 99%
“…The random rotation in all directions results in a net force of zero. Simulation of weightlessness with the RPM was reported to result in a wide variety of cellular responses which have also been found partly under real microgravity conditions (Hoson et al 1997;Schwarzenberg et al 1998;Grimm et al 2002;Uva et al 2002;Infanger et al 2006;Ulbrich et al 2008;Versari et al 2007a, b).…”
Section: Introductionmentioning
confidence: 93%